2018
DOI: 10.21037/jtd.2018.04.39
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of slice-reduced computed tomography on histogram-based densitometry assessment of lung fibrosis in patients with systemic sclerosis

Abstract: Background: To evaluate usability of slice-reduced sequential computed tomography (CT) compared to standard high-resolution CT (HRCT) in patients with systemic sclerosis (SSc) for qualitative and quantitative assessment of interstitial lung disease (ILD) with respect to (I) detection of lung parenchymal abnormalities, (II) qualitative and semiquantitative visual assessment, (III) quantification of ILD by histograms and (IV) accuracy for the 20%-cut off discrimination. Methods: From standard chest HRCT of 60 SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
0
19
0
1
Order By: Relevance
“…Although computed tomography (CT) scans are necessary for diagnosis, they expose patients to radiation [38]. Reduced-dose HRCT protocols may reliably detect SSc-ILD with a much lower radiation exposure than whole-chest HRCT [38,39]. While these reduced-dose protocols have become routine in some centres, further validation in larger cohorts is required.…”
Section: Diagnosis Of Ildmentioning
confidence: 99%
“…Although computed tomography (CT) scans are necessary for diagnosis, they expose patients to radiation [38]. Reduced-dose HRCT protocols may reliably detect SSc-ILD with a much lower radiation exposure than whole-chest HRCT [38,39]. While these reduced-dose protocols have become routine in some centres, further validation in larger cohorts is required.…”
Section: Diagnosis Of Ildmentioning
confidence: 99%
“…The small area where categorized into six categories on the basis of different statistical and fractal texture features. In Delorme, Keller‐Reichenbecher, Zuna, Schlegel, and Van Kaick () and Nguyen‐Kim et al () advocated for the use of a pixel‐based approach for classifying a lung tissue into one of the six classes based on the measures of local texture.…”
Section: Introductionmentioning
confidence: 99%
“…In Delorme, Keller-Reichenbecher, Zuna, Schlegel, and Van Kaick (1997) and Nguyen-Kim et al (2018) advocated for the use of a pixel-based approach for classifying a lung tissue into one of the six classes based on the measures of local texture.…”
mentioning
confidence: 99%
“…[21] Our results expand those of Nguyen-Kim et al, who recently reported that both visual and histogram-based assessment is possible on slice-reduced sequential CT. Histogram parameters such as kurtosis and skewness were capable of discriminating fibrosis (20% cut-off) with high sensitivity and specificity. [53] We included in our analysis the highest strength level for IR, namely SAFIRE 5, reported to provide a so-called “blotchy-appearance”, which could hamper not only visual but also quantitative evaluation of pulmonary abnormalities. We postulate that by applying newer generation of IR (such as model-based IR), effect of TA could be improved.…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that by applying newer generation of IR (such as model-based IR), effect of TA could be improved. [21,53]…”
Section: Discussionmentioning
confidence: 99%